Robust Control of Bench-top Helicopter Using Quantitative Feedback Theory - Ameerul Hakeem Mohd Hairon; Hasmah Mansor; Teddy Surya Gunawan; Sheroz Khan (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
A three degree of freedom (3-DOF) bench-top helicopter is a simplified aerial vehicle which is used to study the behaviors of the helicopter as well as testing multiple flight control approaches for their efficiency. Designing helicopter’s dynamic control is a challenging task due to the presence of high uncertainties and non-linear behavior. In this study, Quantitative Feedback Theory (QFT) is proposed to achieve robust control over the helicopter model. It utilizes frequency domain methodology which ensures plant’s stability by considering the feedback of the system and thus removing the effect of disturbances and reducing sensitivity of parameter’s variation. The proposed technique is tested against LQR-tuned PID controller to demonstrate its procedures as well as its performance. Simulation results obtained through MATLAB Simulink software shown us that QFT algorithm managed to reduce percentage of overshoot and settling time about 50% and 30% respectively over the classical PID controller. DOI: http://dx.doi.org/10.11591/telkomnika.v14i3.7899